Penanaman Nilai-Nilai Akhlak Dalam Pendidikan Islam - Nurhalimah Nurhalimah; Hasanuddin Hasanuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The instillation of moral values ​​is at the heart of Islamic education, emphasizing the development of a holistic human personality characterized by faith, piety, and noble character. In the modern context, Islamic education is not only oriented toward intellectual aspects but also spiritual and moral dimensions. This paper conceptually examines morals in Islam, the urgency of instilling moral values, strategies for developing morals, factors influencing the instillation of moral values, and the challenges of instilling moral values ​​in the modern era. The method used is library research with a descriptive-analytical approach to primary and secondary sources. The results of the study indicate that the formation of noble morals requires integration between formal education, family, and society. Islamic education plays a crucial role in instilling values ​​such as responsibility, honesty, compassion, and trustworthiness through role models, habituation, and a religious humanist approach.